Tinjauan sistem Ekonomi Islam terhadap Rumah Fair Trade Indonesia (Studi Kasus pada APIKRI) - Muhammad Subhan (EPI 15 UMY 080, 2015)
*80 Tinjauan sistem Ekonomi Islam terhadap Rumah Fair Trade Indonesia (Studi Kasus pada APIKRI)